2020
DOI: 10.1111/hsc.13196
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth anxieties in the shadow of COVID‐19: Self‐compassion and social support among Jewish and Arab pregnant women in Israel

Abstract: The study examined two angles of childbirth anxieties of Jewish and Arab pregnant women in Israel during the COVID‐19 pandemic (March‐April, 2020). Specifically, we examined the contribution of personal resources: self‐compassion and perceived social support, as well as a couple of COVID‐19‐related fears of being infected and concern for the foetus, to both the woman's global fear of childbirth (FOC) and her COVID‐19‐related childbirth anxiety. Participants were Jewish and Arab pregnant women ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 61 publications
3
40
0
3
Order By: Relevance
“…There is solid empirical evidence that positive levels of self-compassion improve mental health [ 32 , 33 , 34 , 35 , 79 , 80 , 81 , 82 ] and lessen the negative consequences of psychological parameters such as stress, anxiety, and depression [ 28 , 31 , 34 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. A review of the literature on epidemics that occurred in the last two decades shows that compassion is a positive strategy to deal with the negative impacts of these diseases [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is solid empirical evidence that positive levels of self-compassion improve mental health [ 32 , 33 , 34 , 35 , 79 , 80 , 81 , 82 ] and lessen the negative consequences of psychological parameters such as stress, anxiety, and depression [ 28 , 31 , 34 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. A review of the literature on epidemics that occurred in the last two decades shows that compassion is a positive strategy to deal with the negative impacts of these diseases [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Taubman-Ben-Ari et al's study, which compared Jewish and Arab pregnant women, showed that Arab women reported higher levels of COVID-19-related childbirth anxiety and global fear of childbirth [48]. In research of Gur et al [36], black women were found to be more likely to meet the criteria for depression than white women, but this difference was not significant when accounting for covariates.…”
Section: Demographicmentioning
confidence: 96%
“…Being a woman of color [36,54] Being an Arab woman [48] Education level (high- [49], low- [34,53]) Younger age [36,42] Financial Low income, financial difficulties [25,42] COVID-19-related financial stress and income loss [45,54] Unemployment [34,42] Factors concerning COVID-19…”
Section: Demographicmentioning
confidence: 99%
See 1 more Smart Citation
“…Showing compassion towards the continual uncertainty experienced as a result of the pandemic provides the sense of emotional safety needed to prevent being overtaken by fear. For instance, cross-sectional research demonstrates that people with more self-compassion felt less traumatized by COVID-19 (Jiménez et al, 2020) and had less COVID-19 related anxiety (Mohammadpour et al, 2020;Taubman-Ben-Ari et al, 2020, October 14). In addition, a cross-sectional study in Hong Kong (B. H. P. Lau et al, 2020) found that self-compassion served both a buffering and bolstering role by helping individuals to feel less threatened and distressed about the pandemic (i.e., buffering distress) and also by helping them see potential benefits to the situation such as having more time for relaxation (i.e., bolstering wellbeing).…”
Section: Self-compassionmentioning
confidence: 99%